Boundedness Estimates for Commutators of Riesz Transforms Related to Schrödinger Operators (Analysis in Theory and Applications, 2018)
Let $\mathcal{L} = −∆+V$ be a Schrödinger operator on $\mathbb{R}^n(n ≥ 3)$, where the nonnegativepotential $V$ belongs to reverse Hölder class $RH_{q_1}$ for $q_1 > \frac{n}{2}$. Let $H^p_{\mathcal{L}}(\mathbb{R}^n)$ be the Hardy space associated with $\mathcal{L}$. In this paper, we consider the commutator $[b,T_α]$, which associated with the Riesz transform $T_α = V^α(−∆+V)^{-α}$ with $0
Keywords: Riesz transform; Schrödinger operator; commutator; Campanato space; Hardy space.